Conflict of Interest in the Expansion of Sofifi City in North Maluku, Indonesia - Djen, Risman A.M; Qodir, Zuly (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2023)
Since its 24 years as the capital city of North Maluku province, Sofifi has not had the status of an autonomous region. This study aims to analyse the causes of the emergence of Sofifi's expansion conflict. This study uses a qualitative method with a case study approach. The data sources in this study came from journal articles and online media, which were processed using NVivo 12 Plus. The findings in this study indicate that Sofifi's conflict is a conflict of interest over the struggle for political power and the potential for natural resources by political elites. Even so, the community's demand for the division of Sofifi was based on three things: the reality of backwardness in development, the lack of public services, and the fact that Sofifi is the provincial capital. The emergence of demands for division has given rise to a response of rejection; the refusal is because of the announcement of the Sultanate of Tidore. In addition, there are differences in development governance between the provincial government and the Sultan of Tidore. Later, the Tidore City government also used the argument of a moratorium from the central government to dampen demands for division. This study's conclusion explains the interest in the struggle for power and natural resources behind the emergence of the Sofifi expansion conflict. This study confirms that regional autonomy conflicts tend to be caused by conflicts over power and natural resources that take advantage of ethnicity.